Building a Countrywide Treatment Network: Lessons from Kenya and Zambia - Pollaczek, Lindsay; Mohamed, Habiba; Chomba, Bwalya (Nepal Journal of Obstetrics and Gynaecology, 2018)
In 2014, Fistula Foundation and partners launched Action on Fistula in Kenya, a comprehensive initiative focused on expanding access to fistula care and building the national capacity for fistula treatment, training, and community mobilization. Between May 2014 - September 2018, over 4,000 fistula repair surgeries have been performed at six partner hospitals throughout the country, far surpassing the original targets and nearly doubling the treatment capacity in the country. This was accomplished through partnerships with the Ministry of Health, public and private hospitals, Federation of International Gynecology and Obstetrics for accreditation of the first FIGO obstetric fistula training center in the country, and community-based organizations responsible for patient identification, referral, and reintegration programs. This integrated and holistic model of delivering fistula care has resulted in over 4,100 fistula surgeries performed by 10 Kenyan surgeons, 8 new surgeons trained to the FIGO standard or intermediate competency level, 309 community health volunteers trained and deployed, over 12,000 community events conducted to improve knowledge and awareness of fistula, and over 300 women enrolled in support groups post repair to enhance social and psychological health and boost livelihood development opportunities. The success of the Kenya program prompted the launch of a new countrywide treatment network in Zambia in January 2017. In the first 20 months, the program supported over 375 additional surgeries at six hospitals (from a baseline of approximately 200 surgeries annually done across the country), trained three surgeons to FIGO standard competency level, trained 217 CHVs and Safe Motherhood Action Group Members, and conducted over 2,000 outreach activities for fistula awareness.